Kesiapan Guru Mengemban Kepemimpinan Di Sekolah: Tinjauan Literatur Komparatif Pada Konteks Indonesia, Jepang dan Internasional - Maria Maya Sareng; Erni Murniarti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine teacher readiness to assume leadership roles in schools and to formulate a contextual strengthening model for school improvement. The study used a semi-systematic literature review with comparative content analysis. The review covered 23 scholarly sources selected from an initial pool of 78 documents identified through Google Scholar, SINTA/GARUDA, Scopus, academic publisher websites, and international organization reports. Selection was conducted through duplicate removal, title and abstract screening, full-text eligibility assessment, and relevance mapping based on predefined inclusion and exclusion criteria. The findings show that teacher leadership readiness is a multidimensional construct consisting of cognitive, affective-motivational, socio-collaborative, and structural-institutional dimensions. Critical synthesis indicates that readiness cannot be formed through individual training alone because it depends on the interaction between teacher self-efficacy, professional experience, collaborative culture, principal support, mentoring opportunities, and continuous professional development policies. Comparative analysis shows that Indonesia has policy momentum through Kurikulum Merdeka and Guru Penggerak, but still faces hierarchical and structural barriers. Japan provides an instructive example through kenkyushunin and lesson study, where teacher leadership grows from school-based inquiry and reflective professional routines. This article contributes a layered strengthening model that integrates individual capacity development, professional learning communities, transformational and instructional principal leadership, and institutional policy support.